The Bible and the future - Hoekema, Anthony Andrew, 1913-1988 (Exeter, UK Paternoster, 1979)
Contents : Pt 1 : Inaugerated Eschatology : the eschatological outlook of the Old Testament -- the nature of New Testament eschatology -- the meaning of history -- the Kingdom of God -- the Holy Spirit and Eschatology -- the tension between the already and the not yet; Pt 2 : Future Eschatology : physical death -- immortality -- the intermediate state -- the expectation of the second coming -- the signs of the times -- the signs in particular -- the nature of the second coming -- major millennial views -- a critique of Dispensational Premillennialism -- the millennium of Revelation 20 -- the resurrection of the body -- the final judgement -- eternal punishment -- the New Earth. Includes bibliographical references and index.
Defaced - underlined and comments in margin.
Keywords: Eschatology -- biblical teaching